Sex-Specific Associations of Risks and Cardiac Structure and Function With Microalbumin/Creatinine Ratio in Diastolic Heart Failure - Wei, Fang-Fei; Xue, Ruicong; Wu, Yuzhong; Liang, Weihao; He, Xin; Zhou, Yuanyuan; Owusu-Agyeman, Marvin; Wu, Zexuan; Zhu, Wengen; He, Jiangui; Staessen, Jan A.; Dong, Yugang; et al. (Frontiers in Cardiovascular Medicine, 2020)
Background: Heart failure with preserved ejection fraction (HFpEF) affects women more frequently than men. However, data on sex-specific associations of adverse health outcomes and left ventricular structure and function and with microalbuminuria in patients with HFpEF are scarce. Methods: In 1,334 participants enrolled in the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) Trial, we estimated the sex-specific multivariable-adjusted risk and LV traits with urine microalbumin/creatine ratio (ACR), using Cox or linear regression. Results: In total, 604 (45.3%) were women. In multivariable-adjusted analyses, a doubling of ACR in both men and women was associated with higher posterior (+0.014 cm, p = 0.012/+0.012 cm, p = 0.033) wall thickness and left ventricular mass index (+2.55 mg/m2, p = 0.004/+2.45 mg/m2, p = 0.009), whereas was also associated with higher septal (+0.018 cm, p = 0.002) and left atrial volume index (+1.44 mL/m2, p = 0.001) in men. ACR was a key predictor of all-cause (HR, 1.11; p = 0.006) and cardiovascular (HR, 1.17; p = 0.002) death in women, whereas in men ACR was associated with HF hospitalization (HR, 1.23; p < 0.001), any hospitalization (HR, 1.06; p = 0.006), and myocardial infarction (HR, 1.19; p = 0.017). The interactions of sex with ACR were significant for hospitalization for heart failure and any hospitalization (p ≤ 0.034). Conclusions: Outcomes and cardiac structure and function in patients with HFpEF appear to be influenced by ACR that vary according to sex. In men, ACR was significant associated with LV diastolic function, hospitalization, and myocardial infarction, whereas in women was associated with mortality.